SEED CONDITIONING PROCESS IN THE SANITARY QUALITY OF MARANDU GRASS SEEDS - Jeromini, Tatiane Sanches [UNESP]; Martins, Cibele Chalita [UNESP]; Silva, Givanildo Zildo da; Cruz, Jose de Oliveira (Univ Federal Uberlandia, 2020)
The purpose of seed conditioning process is to separate seeds and their associated structures into different fractions and retain only good and healthy seeds. Thus, the aim of this study was to evaluate the effects the stages of seed conditioning have on the sanitary quality of marandu grass seeds. The seeds were sampled before and during the seed conditioning process, i.e., after exiting the air-screen cleaner and sieves (seeds discharged from the top, middle and bottom sieves), the first gravity separator (seeds drifting around the table, upper and intermediate discharge) and second gravity separator (upper, intermediate and lower discharge). The sanitary analysis was performed using the filter paper method with and without surface disinfestation of the seeds, which were incubated at 20 +/- 2 degrees C, with a photoperiod of 12 hours for seven days. The experiment was conducted in a completely randomized design, in a 2x6 factorial scheme (surface disinfestation x stages of the seed conditioning process) and ten replications. The data was submitted to analysis of variance, using the F test and, when significant, the means of the treatments were compared using the Tukey test at 5% probability. It was concluded that it is not possible to improve the sanitary quality of marandu grass seeds through the seed conditioning process.
Keywords: Blotter test; Brachiaria brizantha; Seed sanity; Seed pathology